UMA INTRODUÇÃO DA EXPERIÊNCIA DA APRENDIZAGEM MEDIADA (EAM) COMO METODOLOGIA PARA O ENSINO DE DESENHO GEOMÉTRICO - JULIANA DE MELO FERRACINI (2021)
This work aims present the result of the research which the objective was to analyze the methodology of mediated learning experience (MLE) applied in Geometric Design teaching as a teaching resource facilitator in the process of teaching-learning Mathematics. Presenting mathematical content in a practical, enjoyable, and real way is essential for building knowledge and applied concepts in everyday life. Geometric Design Teaching through MLE as a didactic Instruct resource allows a different perspective, with a different perspective, transforming learning meaningful to the student. In this context, math activities are proposed using the methodology of mediated learning experience (MLE), because in this way is believed that student learning occurs by a transcendent way. It is observed how important this process is, when the application of the proposed activities was carried out, and in by the data analysis obtained, it is clear that the students have appropriated skills that allowed them to solve easily the proposed questions, refleting the evolution of the teaching-learning process.